Stimulation of innate immune cells Induced by probiotics: participation of toll- like receptors - Maldonado Galdeano, María Carolina (2015)
Objective: The present work aimed to study the functionality of macrophages from different locations (peritoneum, spleen and Peyer´s patches) when they were stimulated with probiotics microorganisms: Lactobacillus casei CRL 431 and Lactobacillus paracasei CNCM I-1518 or a Probiotic Fermented Milk (PFM) through Toll-Like Receptors (TLRs), prior challenged with agonists or antagonists of TLRs. Methods: BALB/c mice received in the drinking water, the probiotic bacteria (L. casei CRL 431 and L. paracasei CNCM I-1518) or the PFM. We focused our investigation mainly on the phagocytic activity of macrophages from peritoneum, spleen and Peyer?s patches and cytokine production were evaluated prior challenged with TLR2 and TLR4 agonists or antagonists. The microbicidal activity of macrophages and against an infection with Salmonella typhimurium was also studied. To assess the role of TLR in probiotic stimulation, we evaluated the phagocytic activity, cytokine production and Immunoglobin G (IgG) anti-OVA in C57BL/6 knockout mice to MyD88, TLR2 and TLR4. Results: In BALB/c mice, the best effect in the phagocytosis assay was obtained with the probiotic bacteria L. casei CRL 431, this effect was reinforced with TLR2 agonist. The production of different cytokines (IL-10 and IL-6) was improved with the probiotic treatments and this production was ameliorated with TLRs agonists. The antimicrobial activity was increased with L. casei CRL 431 and L. paracasei CNCM I-1518, TLR2 and TLR4 antagonists had a negative effect on microbicidal activity. The administration of probiotic bacteria or PFM improved the host response against S. typhimurium controlling the infection during the first hours post-infection. In C57BL/6 knockout mice, phagocytic activity was significantly diminished in comparison to wild type mice and the probiotic bacteria or PFM administration was not able to improve this activity. The IL-10 production was increased at a concentration of 108 cells/ml of L. casei CRL 431 in TLR2-/- and TLR4-/-, but not in MyD88-/- mice. The administration of probiotic bacteria or PFM did not play a stimulating effect in the systemic immune response against to OVA antigen in knockout mice. Conclusions: Probiotics modulate the different signaling pathways of innate immune cells through the TLRs. The macrophages activation depends on location of them and that different probiotic strains of Lactobacilli can evoke different intensity of responses. The data suggest that probiotic not only promote a major expression of TLRs but also use these receptors via the innate immune cells as macrophages to stimulate and modulate the immune response.